Development of Phyllantus acumminatus hairy roots culture system for the production of compounds with biological activity - Garro-Monge, Giovanni (2018)
Plants of the genus Phyllanthus are currently studied because of their ability to produce phenolic compounds with high antioxidant capacity. Additionally, several studies have demonstrated their capability to induce cellular apoptosis through secondary metabolites (phyllanthostatin), which provides these plants a great potential for possible cancer prevention treatments. In this research, P. accuminatus seeds were introduced in vitro, in vitro culture of the seedlings was achieved, and the vitroplants were used in order to induce hairy roots by genetic transformation with Ar15834 of Agrobacterium rhizogenes. The most promising assay for the induction of these organogenic cultures consisted of the use of 1-2 cm stems to which transverse wounds were made in order to inoculate them in the bacterial culture (OD600: 0.6-1). The stems were placed in hormone-free semisolid M & S medium containing 50% of salts and vitamins during 48 hours. After this time, the stems were transferred to a hormone-free semisolid 100% M & S medium supplemented with Ceftriaxona® (500 µg/l) to remove the bacteria. Finally, the hairy roots cultures were accomplished by using hormone-free semisolid 100% M & S medium. Besides, through light microscopy, the established roots morphologic characterization was carried out and it matched the typical hairy roots morphology reported when agro-infection system is used.